Vertical Handover Study on 4G Category Vs 5G Category for 3GPP Generation Mobile Systems and Non-3GPP Wireless Networks - Khattab, Omar (Discoveries in Agriculture and Food Sciences, 2018)
Nowadays, wireless communication technologies have become an integral part of people’s daily life and businesses all over the world. Due to the rapid increase in the number of the Mobile Users (MUs) who demand the service of communicating via wireless access networks, the wireless communication technologies have evolved from the first generation to the fifth generation. The Next Generation Wireless Systems (NGWSs) consists of heterogeneous wireless access networks of 3GPP generation mobile Systems (e.g., UMTS, LTE) and non-3GPP wireless networks (e.g., WiFi, WiMAX), where MUs can access these technologies and services using a single device. This paper presents a study for Vertical Handover (VHO) approaches of 3GPP and non-3GPP proposed in the literature and classifies them into two categories for which their characteristics are discussed.